2019
DOI: 10.1158/1078-0432.ccr-19-1126
|View full text |Cite
|
Sign up to set email alerts
|

Tissue and Plasma EGFR Mutation Analysis in the FLAURA Trial: Osimertinib versus Comparator EGFR Tyrosine Kinase Inhibitor as First-Line Treatment in Patients with EGFR-Mutated Advanced Non–Small Cell Lung Cancer

Abstract: Purpose: To assess the utility of the cobas EGFR Mutation Test, with tissue and plasma, for first-line osimertinib therapy for patients with EGFR-mutated (EGFRm; Ex19del and/or L858R) advanced or metastatic non-small cell lung cancer (NSCLC) from the FLAURA study (NCT02296125).Experimental Design: Tumor tissue EGFRm status was determined at screening using the central cobas tissue test or a local tissue test. Baseline circulating tumor (ct)DNA EGFRm status was retrospectively determined with the central cobas … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
96
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 44 publications
(46 reference statements)
8
96
0
Order By: Relevance
“…At the time of clinical diagnosis, the detection of EGFR mutations in tumor tissue or ctDNA, when tissue is unavailable, is mandatory for the selection of patients [1,2]. Several studies have shown a high concordance between the presence of EGFR mutations in tissue and plasma, especially in patients with diffuse metastatic disease [3,4]. A limited number of studies conducted with quantitative of semi-quantitative mutation detection methods have suggested a correlation between the amount of the sensitizing EGFR mutant allele (sEGFRma) in plasma and tumor burden [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…At the time of clinical diagnosis, the detection of EGFR mutations in tumor tissue or ctDNA, when tissue is unavailable, is mandatory for the selection of patients [1,2]. Several studies have shown a high concordance between the presence of EGFR mutations in tissue and plasma, especially in patients with diffuse metastatic disease [3,4]. A limited number of studies conducted with quantitative of semi-quantitative mutation detection methods have suggested a correlation between the amount of the sensitizing EGFR mutant allele (sEGFRma) in plasma and tumor burden [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…For the validation of ctDNA using UltraSEEK™ and ddPCR analyses, ccfDNA was extracted from 4 mL (MTP cohort) and 2 mL (GRO cohort) of the same cell-free plasma used for the diagnostic Cobas test and eluted in 100 µL (MTP cohort) and 52 µL (GRO cohort) of elution buffer using the QIAamp Circulating Nucleic Acid Kit (Qiagen, Hilden, Germany) according to the manufacturer’s recommendations as reported previously [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. CcfDNA yield was determined with either the LabChip ® GX Touch™ Nucleic Acid Analyzer (PerkinElmer, Waltham, MA, USA; MTP cohort) or the Qubit™ 1× dsDNA HS Assay Kit (Thermofisher Scientific, Waltham, MA, USA; GRO cohort).…”
Section: Methodsmentioning
confidence: 99%
“…To date, only one of the very few FDA-approved ccfDNA-based tests with clinical utility is the Cobas ® EGFR Mutation Test v2 (Roche Molecular Systems Inc., Pleasanton, CA, USA) detecting 42 EGFR hotspot mutations in ccfDNA from patients with lung cancer [ 5 , 18 , 19 , 20 , 21 , 22 ]. The Cobas ® test is approved as a companion diagnostic test on cell-free plasma to select NSCLC patients eligible for EGFR-TKI, including osimertinib [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…For patients with advanced disease, ctDNA test results appear more reliable when performed at disease progression rather than during response to therapy [32]. This implies that confirmation of ctDNA negative tests is still recommended using tumor biopsy [1,41,49]. At the other end, false-positive findings can be introduced due to the presence of cfDNA from multiple sources, including age-related mutations from hematopoietic cells that and ctDNA mutations that are shared between cancer and benign conditions [41].…”
Section: Liquid Versus Tissue Biopsiesmentioning
confidence: 99%
“…Tumor type and metastatic sites, stage of disease, tumor heterogeneity, time of sampling, and clonal versus subclonal variants can influence assay detection capacities independently of analytical factors [22,32]. Notably, ctDNA yields are lower at the early stages of cancer and non-detectable for certain types of cancers like neoplasms of the central nervous system, which can limit the utility of ctDNA in these cases [23,49]. For patients with advanced disease, ctDNA test results appear more reliable when performed at disease progression rather than during response to therapy [32].…”
Section: Liquid Versus Tissue Biopsiesmentioning
confidence: 99%